Management of low back pain: Treatment provision within private practice in the UK in the context of clinical guidelines. (13th March 2021) - Murtagh, Shemane; Bryant, Elizabeth; Hebron, Clair; Ridehalgh, Colette; Horler, Christopher; Trosh, Caroline; Olivier, George
Abstract: Objective: To summarise the combination of treatments private UK‐based physiotherapists use with patients who have low back pain (LBP) and the extent to which the treatments used are consistent with clinical guideline recommendations. Design: Cross‐sectional observational survey. Methods: Data were collected from physiotherapists within private UK‐based clinics using an online standardised data collection system to record the treatment they provided for patients who had LBP with/without leg pain. Treatment data were classified into those that are 'recommended', 'not recommended' and had 'no recommendation'. Results/Findings: Treatment provided to 8003 patients were included in the analyses. Most patients (95.0%) were provided with a 'recommended' treatment. Approximately half of the patients who received 'recommended' treatment were also provided with other treatments that were either 'not recommended' (16.7%), had 'no recommendation' (16.6%) or a combination of both (13.0%). Few patients were provided with only treatments that were 'not recommended' and/or treatment with 'no recommendation' (4.6%). Conclusion: This study provides insight into the self‐reported practice of participating physiotherapists and highlights how they generally adopted a multimodal treatment model for patients with LBP. Consistent with the National Institute for Health and Care Excellence guidelines, most patients received information and advice often in conjunction with exercise and manual therapy. Only a small proportion of patients were provided with treatments that are 'not recommended' and/or treatment that had 'no recommendation'. These findings are useful in documenting the implementation of clinical guidelines given the need for practitioners to balance the best available evidence with patient expectation and preference and to facilitate the therapeutic alliance.